Children's interactive storytelling in Virtual Reality. Issue 1 (March 2021) - Yamada-Rice, Dylan
This article reports on one stage of a project that considered twenty 8–12-years-olds use of Virtual Reality (VR) for entertainment. The entire project considered this in relation to interaction and engagement, health and safety and how VR play fitted into children's everyday home lives. The specific focus of this article is solely on children's interaction and engagement with a range of VR content on both a low-end and high-end head mounted display (HMD). The data were analysed using novel multimodal methods that included stop-motion animation and graphic narratives to develop multimodal means for analysis within the context of VR. The data highlighted core design elements in VR content that promoted or inhibited children's storytelling in virtual worlds. These are visual style, movement and sound which are described in relation to three core points of the user's journey through the virtual story; (1) entering the virtual environment, (2) being in the virtual story world, and (3) affecting the story through interactive objects. The findings offer research-based design implications for the improvement of virtual content for children, specifically in relation to creating content that promotes creativity and storytelling, thereby extending the benefits that have previously been highlighted in the field of interactive storytelling with other digital media.